2021
DOI: 10.1080/2162402x.2021.1920739
|View full text |Cite
|
Sign up to set email alerts
|

Activity-regulated cytoskeleton-associated protein/activity-regulated gene 3.1 (Arc/Arg3.1) enhances dendritic cell vaccination in experimental melanoma

Abstract: Sahm (2021) Activity-regulated cytoskeleton-associated protein/activity-regulated gene 3.1 (Arc/Arg3.1) enhances dendritic cell vaccination in experimental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Cacnb3 deficiency resulted in an impaired ATPinduced migration, whereas baseline and LPS-mediated migration were not affected. This is particularly noteworthy as our previous findings showed impaired steady-state and LPS-induced migration in Arc-deficient BMDCs (7,39). The specific impairment of ATPdependent migration is consistent with studies that showed different migratory patterns between PAMP and DAMP exposure (40).…”
Section: Discussionsupporting
confidence: 90%
“…Cacnb3 deficiency resulted in an impaired ATPinduced migration, whereas baseline and LPS-mediated migration were not affected. This is particularly noteworthy as our previous findings showed impaired steady-state and LPS-induced migration in Arc-deficient BMDCs (7,39). The specific impairment of ATPdependent migration is consistent with studies that showed different migratory patterns between PAMP and DAMP exposure (40).…”
Section: Discussionsupporting
confidence: 90%